A Chinese Perspective on Writing English Abstracts: Challenges, Errors, Improvement Tips, and Critical Reflections - Bin Chen; Jinyan Huang (SAGE Open, 2023)
This study examined Chinese EFL researchers’ English abstract writing in language education. Using open-ended questionnaires, it first investigated 24 Chinese EFL researchers’ perceptions of their challenges in writing English abstracts. Using generalizability theory and follow-up interviews, it then invited 16 experienced English journal reviewers to assess 27 published English abstracts written by Chinese EFL researchers to identify common errors and suggest improvement tips. Finally, it examined eight selected Chinese EFL researchers’ critical reflections on the English journal reviewers’ assessment of the 27 English abstracts. The results indicated that Chinese EFL researchers experienced several challenges in writing English abstracts. Further, the English reviewers’ assessment of the 27 abstracts was consistent and reliable. The common errors were associated with the accuracy, non-evaluative nature, coherence and readability, and conciseness of an English abstract. The English reviewers provided tips for improvement, and Chinese EFL researchers expressed their critical reflections on their assessment. Educational implications are discussed.